NON-OBSTRUCTIVE CORONARIES IN PATIENTS PRESENTING WITH THE NON ST-ELEVATION ACUTE CORONARY SYNDROME - Zada, Shakir; Bhatti, Khalid Iqbal; Zeb, Muhammad; Pirah, Romana; Musaddiq, Daniyal; Memon, Aziz ur Rehman (Journal of Ayub Medical College Abbottabad, 2023)
Background: Worldwide, cardiovascular diseases are the major cause of mortality and morbidity with acute coronary syndrome as the most common clinical manifestation. In a typical clinical setup, around 30% of the patients presented with ST-segment elevation myocardial infarction (STEMI) caused by the complete occlusion of the coronary artery and the remaining 70% with intermittent or partial occlusion of the coronary termed as non-ST elevation The aim of this study was to assess the prevalence and characteristics of non-obstructive coronary arteries among patients presenting with non ST-elevation acute coronary syndrome (NSTE-ACS) at a tertiary care cardiac center of Karachi, Pakistan. Methods: This was a descriptive cross-sectional study, conducted at a tertiary care hospital in Karachi. Study inclusion criteria were patients of either gender admitted with NSTE-ACS and age between 30-70 years. A routine coronary angiogram was performed in all the patients and the absence of ‰¥50% stenosis in any major epicardial vessel was taken in non-obstructive coronaries. Results: A total of 174 patients (30-70 years) were included, of which 99 (56.9%) were male and the mean age was 59.43±11.24 years. In the distribution of socioeconomic status, 54 (31.0%) were lower class, middle class 81 (46.6%) while upper-class status were 39 (22.4%). Hypertension was observed in 76 (43.7%), chronic kidney disease in 20 (11.5%), and hyperlipidemia in 55 (31.6%). Non-obstructive coronary arteries were noted in 25 (14.4%) patients. Conclusion: It is to be concluded that non-obstructive coronary arteries are fairly prevalent in patients arriving in hospital with NSTE-ACS in our population. Further research is needed to better understand the underlying pathophysiology and optimal management strategies for patients with NOCA in the setting of NSTEMI.